2014
DOI: 10.1111/add.12486
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the economic impact of smoking bans in restaurants and bars

Abstract: Meta-analysis of the economic impact of smoking bans in hospitality sector showed overall no substantial economic gains or losses. Differential impacts were observed across individual business types and outcome variable, but at aggregate level these appear to balance out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 5 publications
4
16
0
Order By: Relevance
“…On one hand, the results are in accordance with a large part of those results found in the literature focused on European countries performed by Scollo, Lal, and Glantz (), Scollo and Lal (), and Cornelsen et al. (), although they mainly referred to aggregate data on tax revenues, employment, and sales. On the other hand, the present results are partially in contrast with what has been found in the United States where some studies suggested that smoking bans had a statistically significant negative effect (or exceptionally positive effects on employment) on the economic activity of the hospitality sector.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On one hand, the results are in accordance with a large part of those results found in the literature focused on European countries performed by Scollo, Lal, and Glantz (), Scollo and Lal (), and Cornelsen et al. (), although they mainly referred to aggregate data on tax revenues, employment, and sales. On the other hand, the present results are partially in contrast with what has been found in the United States where some studies suggested that smoking bans had a statistically significant negative effect (or exceptionally positive effects on employment) on the economic activity of the hospitality sector.…”
Section: Discussionsupporting
confidence: 91%
“…Another crucial point is that we considered only comprehensive smoking bans applied at the country level, avoiding the problems discussed by Cornelsen et al. (). These authors argued that the mixed effects found in the United States can be explained by differences in the type of smoking ban analyzed (comprehensive or partial), in the type of business (bars or restaurants), or in the territorial level to which the bans are applied (countries, municipalities, or cities).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 An additional five states have smoke-free air laws covering only restaurants, representing more than a tenth of the population (12.0%). 8 Despite the rapid expansion of smoke-free air laws during the 2000s, 9 strong public support 10 11 and a near consensus among peer-reviewed studies that smoke-free air laws have generally null or positive economic effects, 12 legislative progress on this issue has stalled in recent years and even regressed in some cases. 13 Population coverage by comprehensive smoke-free air laws has barely changed since 2010 and perhaps counter-intuitively, states with pre-existing non-comprehensive laws are less likely to subsequently pass a more comprehensive law in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other parts of the world have demonstrated that smoke-free policies do not reduce revenue in hospitality venues over time [24][25][26][27] . Many of the respondents in our study erroneously felt that the "State regulation of smoking law" would decrease revenue.…”
Section: Discussionmentioning
confidence: 99%